Sundby glashytta och Glashytteuddden utanför Örebro - Karlenby, Leif (Hikuin, 2010)
The archaeological excavation of Sundby glasworks outside Örebro By Leif Karlenby The glass production in Sweden developed into an industry during the late 16th and early 17th centuries. One of the first glassworks to be established was founded in 1592 in Sundby by Karl IX of Sweden. This was superseded by another one at the nearby Glashytteudden. This was established by a merchant, Påvel Jung, who had recently arrived from Nyköping, with the sole purpose of starting a glass works. His son, Melchior Jung, later became the founder of the first glassworks in Stockholm. In this way it is possible to establish an unbroken tradition from the royal glassworks at Nyköping and Sundby to the mercantile pre-industrial glassworks of the Jung’s to the beginning of glass industry in Sweden. During two weeks in the summer 2006 excavations were performed in Sundby. It had been started by Duke Karl, soon to be king Karl IX to produce window- and drinking glasses for the Örebro castle. The kiln was preserved in parts of up to a meter in height. We excavated the northern part where the remains of the cooling kiln were found. It had been torn down when it no longer worked properly and below it the fundaments of several more kilns were found. The production consisted of both window glass and drinking vessels, that showed a great variation in style. They were similar to glasses produced in all of northern Europe, and maybe that is not so strange since the glassblowers came from Germany and Holland. A large part of the find material was shards from pharmacy equipment and a lot of shards came from broken bottles, with dark green or brown and thick walls.